The short story «Cera» by César Vallejo and the brief narrative by Edgar Allan Poe - Mejía Farje, Antonio (2023)
This research comparatively analyses the short story «Cera», from the book Escalas (1923), by César Vallejo. It compares elements contained in the first edition version with three short stories by the American writer Edgar Allan Poe: «William Wilson» (1839), «The Black Cat» (1843) and «The Tell-Tale Heart» (1843). The analysis covers: (a) the topic of the double, (b) the use of the unreliable narrator and (c) the practice of snooping. These elements are also briefly reconsidered from the variants in the Couffon manuscript version, whose numerous deletions modify the above elements. Finally, the research proposes a three-part segmentation of the story structure and a central conflict between chance and fate, based on the symbol of the dice.